Educational Advisor in Brazil and its performance for a critical and quality education (Praxis Educativa, 2017)
The present work intends to analyze the current educational advisor’s insertionin the Brazilian contemporary education, noting its relation with the construction of democratic management and improves the quality of public schools in Brazil. We intend to demonstrate, through reading and criticism of the legislation and relevantliterature that the action of the educational advisor can (and every day it becomes more obvious that) to help students exercise in a critical way their citizenship.
Keywords: educational advisor; democratic management; citizenship; public school network; Law of Guidelines and Bases.